Biofortification and growth enhancement of wheat via bacteria-assisted iron and zinc nanoparticles - Pradeep Kumar; Anuj Rana; Mansi Sheokand; Suresh Kumar; Kautilya Chaudhary; Urvashi Nandal; Sandeep Kumar; Rahul Kumar Dhaka (Frontiers in Nanotechnology)
This study reports the isolation of four bacteria from metal-enriched sites and rhizosphere soil and evaluated their tolerance (to 9 mM) toward iron (ferric chloride) and zinc (zinc sulfate). Among all the four isolates, AW5 exhibited plant growth-promoting (PGP) traits, namely, siderophores, indole-3-acetic acid, and increased solubilization of zinc and phosphorus. AW5 efficiently synthesized iron and zinc nanoparticles (NPs) of size 135 nm and 197 nm, respectively. The biologically synthesized iron and zinc NPs (20 ppm) enhanced the bacteria (AW5) growth, production of indole-3-acetic acid and siderophore, and solubilization of phosphate and zinc. A combination of plant growth-promoting rhizobacteria (PGPR) and NPs (seed priming) significantly improved shoot (up to 9%) and root length (up to 35%), wheat dry biomass (up to 96%), 100-grain weight (up to 28%), iron content (14%), and zinc content (4%) versus the recommended dose of fertilizer (RDF) control under a pot experiment. A foliar spray of NPs combined with PGPR seed priming showed a significant increase in shoot length (7%) and root length (up to 14%), wheat dry biomass (up to 59%), 100-grain weight (up to 34%), iron content (27%), and zinc content (53%) versus the RDF control under a pot experiment. Nanoparticle treatment through seed priming or foliar spray enhanced plant growth hormones (auxin, 59%) and chlorophyll A and B (51% and 107%) and soil microbial enzymes (dehydrogenase up to 53% and fluorescein diacetate up to 164%), and increased grain fat (65%) and ash content (42%). The synthesized NPs improved root morphology, photosynthesis, and soil enzymatic activities that enhanced the availability of micronutrients from soil to plant for its growth and biofortification. The synergistic impact of NPs bolstered plant–bacteria interactions, hence increasing nutrient uptake by improving the root architecture and facilitating the availability of FeNPs and ZnNPs. This study provides valuable insights into employing bacteria-assisted NPs in biofortification and crop productivity to achieve agricultural sustainability.